(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides information on the importance of the English language and its role in the world. This article also explains the importance of English in the field of medicine, first of all, along with the stages of becoming a doctor, and through many methods on how to learn English quickly and easily in medical institutions.